2011
DOI: 10.5402/2011/195846
|View full text |Cite
|
Sign up to set email alerts
|

Airway Epithelium in Atopic and Nonatopic Asthma: Similarities and Differences

Abstract: Asthma is an inflammatory disorder of the airways, and the airway epithelium has the central role in its pathogenesis. In general, the airway inflammation is characterised by the infiltration of the epithelium and submucosa by a range of inflammatory cells driven largely by Th-2 lymphocytes, eosinophils, and mast cells. The pathogenic mechanisms of nonatopic asthma in comparison to its atopic counterpart have always been a subject of debate. Although clinically are two distinct entities, more similarities than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
0
18
0
3
Order By: Relevance
“…[ 27 28 ] We and others have previously reported that the expression of some CXC and CC cheomokines and their receptors are elevated in airways of asthma in a limited numbers of subjects. [ 10 29 30 31 ] Thus, in the present study, we also analyzed a number of CXC and CC motif chemokines in the BALF of asthmatics and controls. Our data showed that the median concentrations of CXCL10 (IP-10), CCL11 (eotaxin), CCL17 (TARC), and CCL4 (MIP-1) were significantly elevated in the BALF of asthmatics compared with controls, with increases accompanying disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 28 ] We and others have previously reported that the expression of some CXC and CC cheomokines and their receptors are elevated in airways of asthma in a limited numbers of subjects. [ 10 29 30 31 ] Thus, in the present study, we also analyzed a number of CXC and CC motif chemokines in the BALF of asthmatics and controls. Our data showed that the median concentrations of CXCL10 (IP-10), CCL11 (eotaxin), CCL17 (TARC), and CCL4 (MIP-1) were significantly elevated in the BALF of asthmatics compared with controls, with increases accompanying disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…There is ongoing debate as to whether atopic asthma and non-atopic asthma are two immunopathologically distinct entities or if both are driven by similar mechanisms [37]. There is evidence supporting the concept that IgE-mediated mechanisms play a major role in asthma pathogenesis.…”
Section: Fibrinolysismentioning
confidence: 99%
“…For example, in cases of allergic asthma, environmental control is performed differently, and patients can benefit from anti-IgE and immunotherapy [21,22]. …”
Section: Introductionmentioning
confidence: 99%